2002
DOI: 10.1002/hc.10083
|View full text |Cite
|
Sign up to set email alerts
|

2,4,6‐Tri‐tert‐butylphenyl and 2,4‐di‐tert‐butyl‐6‐methylphenyl groups: Look similar, react differently

Abstract: The crystal structures of molecules with two phosphaalkene groups have been determined. Differences in the stabilization of the P C π-bond by the 2,4,6-tri-tert-butylphenyl and 2,4-di-tert-butyl-6-methylphenyl groups were observed. It has been found that lithium supermesityl(trimethylsilyl)phosphide could be a very efficient base to remove a proton from acetonitrile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 17 publications
(16 reference statements)
0
23
0
Order By: Relevance
“…This is in marked contrast to the only other uncomplexed pyridylbisphosphaalkene which has been structurally characterized, i.e. II (Scheme 1), in which the PC units are twisted by as much as 63° [8]. This significant twisting limits the electronic interaction between the PC units and the central aromatic ring so that no conjugation can be expected for II .…”
Section: Resultsmentioning
confidence: 83%
“…This is in marked contrast to the only other uncomplexed pyridylbisphosphaalkene which has been structurally characterized, i.e. II (Scheme 1), in which the PC units are twisted by as much as 63° [8]. This significant twisting limits the electronic interaction between the PC units and the central aromatic ring so that no conjugation can be expected for II .…”
Section: Resultsmentioning
confidence: 83%
“…The crude product was recrystallized from n-pentane to afford colorless crystals of 1 a (52 %), which were characterized crystallographically. The optical activity of the product was confirmed by polarimetry and the Flack parameter [0.13 (9)], determined crystallo- graphically, suggested that the S configuration of 1 a was assigned correctly. Moreover, all of the compounds leading to phosphaalkene 1 a were similarly optically active.…”
Section: Resultsmentioning
confidence: 99%
“…
CHPh} y ] n (9 a: x = 0.13n, y = 0.87n; GPC: M w = 7400 g mol À1 , PDI = 1.15).(1,3)-butadiene B, [7] phosphinidene-imine C, [8] and 2,6-bis-(phosphaethenyl)pyridine D. [9] These ligands incorporate the bulky Mes* substituent, and the effects of this large group on mechanistic processes relevant to catalysis (ligand exchange, substrate binding, turnover, etc.) are not well understood.
…”
mentioning
confidence: 99%
“…A further 31 structures proved to have questionable values for density or a dubious structure as identified in the CSD or by using the CheckCIF online program and 27 structures could not be evaluated because of insufficient data (i.e., no available cif). The following structures satisfy the search criteria and are potential candidates for purely organic microporous crystals: ABINOP, [31] BALNIM, [24] EFALEC, [32] FAKTIV, [33] GIPTOO, [34] KETYEO, [35] NASQAA, [36] PETREM, [37] RERNEI, [38] SULDUY [39] TOZZIR, [40] WAVJAE, [41] XICRUW, [42] XOPYEG, [43] and YUPTIM. [44] In addition, the following metal-containing structures are candidates as microporous molecular crystals: ADIYIV, [45] FOSTEM, [46] FOSTEM10, [47] GOBSUL, [47] IKANOX, [48] KISYIV, [49] PICKAN, [50] and TIKFIC.…”
Section: Methodsmentioning
confidence: 99%